Pengaruh Implementasi Pembelajaran Al-Quran Metode Ummi Terhadap Makhorijul Huruf Dan Tajwid - Lutfi Ridho; Muhammad Mahfud; Muhammad Arifuddin (Jurnal Pendidikan Agama Islam Miazhar, 2023)
In memorizing the al-Quran there are many kidness obtaind by memorizers of thr al-Quran. The kidness can be obtained in this woid and in the hereafter. But there are several obstacles for memorizers of the al-Quran. The ability to master makhorijul huruf and tajwid is required. Because errors in pronunciation can change the meaning and even the intent of the verse being read. MI KH. Abu Mansur Lidah Wetan Surabaya apply the Ummi method in learning the al-Quran. In the research we want to know how much influnece the Ummi method of lerning the al-Quran has on the makhorijul huruf and tajeid of tahfidz claa students. This study used quantitative methods with a sample of 35 students and to obtan research data using questionnaires and oral test. The result is that the variabel X to Y1 gets a significance 0,179 > 0,05 mans the implementation of learning al-Quran Ummi method MI KH. Abu Mansur Lidah Wetan Surabaya in The class Tahfidz has no effect. While the variable X to Y2 gets a significance 0,025 ˂ 0,05 Meaning that the implementation of learning al-Quran Ummi method MI KH. Abu Mansur Lidah Wetan Surabaya in The class Tahfidz has effect of 14,3%.",